Outcome of Posterior Sagital Ano Recto Plasty (PSARP) In Anorectal Malformation: Our Experience at tertiary care hospital M.T.I/L.R.H Peshawar - Muhammad Younas Khan, Syed Asad Maroof, Fayaz Iqbal, Wardah Saleem, Muhmmand Shoaib, Kifayat (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study aimed to evaluate the functional result of pediatric patients at MTI / LRH, Peshawar, who had Posterior Sagittal Anorectoplasty (PSARP) for anorectal abnormalities. Methods: Three hundred and fifty cases with anorectal anomalies were analyzed in this research from 2017 to 2021 at MTI/Lady Reading Hospital Peshawar. Except for female patients with rectogenital tract fistula, distal logograms were regularly done on all patients. Each patient diagnosed with an intermediate, high-type, or cloacal malformation underwent PSARP. Both intraoperative and postoperative mortality and morbidity rates were documented. Following the PSARP treatment, patients should continue to have their anesthetics dilated regularly for three to six months after discharge. Six months to a year of patient follow-up was conducted. Results: Three hundred and fifty patients (12–36 months of age) participated in the study (245 males and 110 girls). All patients had PSARP done. One hundred ninety-five males were diagnosed with a rectourethral fistula, 95 girls with a genitourinary tract fistula, and five girls with a cloacal malformation. There was a 2.5% death rate (9/35 operations) from the surgery and its aftermath. At the outset of treatment, 30% of patients had excellent outcomes, 45% experienced fair results, and 25% experienced poor outcomes. Ninety-nine individuals had chronic constipation, and 35 had anal stenosis. Sixty individuals had mucosal prolapse and perineal irritation. In 5 patients, recurrent UTIs occurred, and in 3 cases, orchitis. The urethral stricture was discovered in two patients, and a urethral diverticulum was identified, necessitating revision surgery. Practical implication: The recorded data outcomes will be useful for the surgeons in the same setting. Conclusion: Most severe and mild anorectal abnormalities were seen in male infants. Regarding bowel control, PSARP surgery is a safe option with positive functional outcomes. Keywords: Anorectal Malformation, Anomalies, Posterior Sagittal Anorectoplasty, Pull Through, Faecal Continence, Constipation.